Vertically integrated, double stack oxide TFT layers for high‐resolution AMOLED backplane. Issue 6 (4th May 2020) - Lee, Suhui; Chen, Yuanfeng; Kim, Jeonggi; Jang, Jin
Abstract: We developed a novel vertically integrated, double stack oxide thin‐film transistor (TFT) backplane for high‐resolution organic light‐emitting diode (OLED) displays. The first TFT layer is bulk‐accumulation mode, and the second TFT layer is a single gate with back‐channel etched structure. The extracted mobilities and threshold voltages are higher than 10 cm 2 /Vs and 0 ~ 1 V, respectively. Both TFTs are found to be extremely stable under the bias and temperature stress. The gate driver with width of 530 μm and a pitch of 18.6 μm was developed, exhibiting well shifted signal up to the last stage of 900 stages without output degradation, which could be used for 1360 ppi TFT backplane. Abstract : We developed a novel vertically integrated, double stack oxide thin‐film transistor (TFT) backplane for high resolution OLED displays. This structure is based on the conventional back‐channel etched TFT. Both TFTs located at different layers are found to be extremely stable under the bias and temperature stress. We demonstrated a 1.2″ (1360 ppi) a‐IGZO TFT backplane with the gate driver integrated.